Identification and targeting of an interaction between a tyrosine motif within hepatitis C virus core protein and AP2M1 essential for viral assembly. - Gregory Neveu (Public Library of Science (PLoS), 2012)
Novel therapies are urgently needed against hepatitis C virus infection (HCV), a major global health problem. The current model of infectious virus production suggests that HCV virions are assembled on or near the surface of lipid droplets, acquire their envelope at the ER, and egress through the secretory pathway. The mechanisms of HCV assembly and particularly the role of viral-host protein-protein interactions in mediating this process are, however, poorly understood. We identified a conserved heretofore unrecognized YXXΦ motif (Φ is a bulky hydrophobic residue) within the core protein. This motif is homologous to sorting signals within host cargo proteins known to mediate binding of AP2M1, the μ subunit of clathrin adaptor protein complex 2 (AP-2), and intracellular trafficking. Using microfluidics affinity analysis, protein-fragment complementation assays, and co-immunoprecipitations in infected cells, we show that this motif mediates core binding to AP2M1. YXXΦ mutations, silencing AP2M1 expression or overexpressing a dominant negative AP2M1 mutant had no effect on HCV RNA replication, however, they dramatically inhibited intra- and extracellular infectivity, consistent with a defect in viral assembly. Quantitative confocal immunofluorescence analysis revealed that core's YXXΦ motif mediates recruitment of AP2M1 to lipid droplets and that the observed defect in HCV assembly following disruption of core-AP2M1 binding correlates with accumulation of core on lipid droplets, reduced core colocalization with E2 and reduced core localization to trans-Golgi network (TGN), the presumed site of viral particles maturation. Furthermore, AAK1 and GAK, serine/threonine kinases known to stimulate binding of AP2M1 to host cargo proteins, regulate core-AP2M1 binding and are essential for HCV assembly. Last, approved anti-cancer drugs that inhibit AAK1 or GAK not only disrupt core-AP2M1 binding, but also significantly inhibit HCV assembly and infectious virus production. These results validate viral-host interactions essential for HCV assembly and yield compounds for pharmaceutical development.